Progress in understanding mechanisms of opioid-induced gastrointestinal adverse effects and respiratory depression. (15th March 2018) - Imam, Mohammad Zafar; Kuo, Andy; Ghassabian, Sussan; Smith, Maree T.
Abstract: Opioids evoke analgesia through activation of opioid receptors (predominantly the μ opioid receptor) in the central nervous system. Opioid receptors are abundant in multiple regions of the central nervous system and the peripheral nervous system including enteric neurons. Opioid-related adverse effects such as constipation, nausea, and vomiting pose challenges for compliance and continuation of the therapy for chronic pain management. In the post-operative setting opioid-induced depression of respiration can be fatal. These critical limitations warrant a better understanding of their underpinning cellular and molecular mechanisms to inform the design of novel opioid analgesic molecules that are devoid of these unwanted side-effects. Research efforts on opioid receptor signalling in the past decade suggest that differential signalling pathways and downstream molecules preferentially mediate distinct pharmacological effects. Additionally, interaction among opioid receptors and, between opioid receptor and non-opioid receptors to form signalling complexes shows that opioid-induced receptor signalling is potentially more complicated than previously thought. This complexity provides an opportunity to identify and probe relationships between selective signalling pathway specificity and in vivo production of opioid-related adverse effects. In this review, we focus on current knowledge of the mechanisms thought to transduce opioid-induced gastrointestinal adverse effects (constipation, nausea, vomiting) and respiratory depression. Highlights: Review of currently understood mechanisms of opioid-related gastrointestinal and respiratory side-effects. The cellular mechanisms underpinning these opioid related side-effects are poorly understood. New insight on these mechanisms is opening new frontiers for discovery of novel opioids with improved side effects profile.